Establishment Code Hand Palm (Palm Code) 2D Gabor-Based Method - Darma Putra, I Ketut Gede; Bhuana, Wira; Erdiawan, Erdiawan (Makara Journal of Technology, 2011)
Establishment Code Hand Palm (Palm Code) 2D Gabor-Based Method. Palmprint is relatively new in physiological biometrics. Palmprint ROI segmentation and feature extraction are two important issues in palm print recognition. This paper introduces two steps in the center of mass moment method for ROI segmentation that will be applied in the Gabor 2D filter to obtain palm code as palmprint feature vector. Normalized Hamming distance was used to measure the similarity degrees of two feature vectors of palmprint. The system was tested using database 1000 palmprint images generated from 5 samples from each of the 200 persons randomly selected with ROI 64 x 64 and 128 x 128 pixel. Experiment results show that this system can achieve high performance with a success rate about 98.7% (FRR = 1.17%, FAR = 0.11%, T = 0.376) with ROI 64 x 64 pixel.